FACTORS THAT INFLUENCE PERFORMANCE - Pelix Van Bosco Purba; Kiki Farida Ferine (Universitas Efarina, 2025)
This study aims to analyze the influence of training, competence, and work effectiveness on employee performance, with moderation variables strengthening the relationship among these variables. The research was conducted at PT PLN (Persero) North Sumatra Distribution Management Implementation Unit (UP2D). The population consisted of 47 employees, and due to the relatively small population size, the saturated sampling technique was used, where the entire population was taken as the sample. The data analysis method applied a quantitative approach using the SmartPLS software. The results indicate that training has a negative and insignificant effect on employee performance, while competence and work effectiveness have a positive and significant effect. Additionally, the first moderating effect shows a negative and significant influence, whereas the second moderating effect has a positive but insignificant influence on performance. These findings suggest that in order to improve employee performance, the company should focus on enhancing employee competence and work effectiveness, while also evaluating training programs and moderating factors that affect the relationships among the variables studied.